SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN SDN 1 PESAWAHAN - Yurnida (UNISAN JURNAL, 2024)
Academic supervision carried out by the head of SDN 1 Pesawahan is an effort to improve the quality of learning through coaching and guidance to teachers in planning learning, implementing the learning process, and evaluating student learning outcomes in order to achieve predetermined goals. The academic supervision program for the head of SDN 1 Pesawahan was prepared based on the results of supervision analysis and monitoring of previous learning processes; The principal’s academic supervision program is prepared at the beginning of the school year, by first identifying problems, determining objectives and determining the time for implementation, involving the deputy head of curriculum, deputy head of quality assurance, and teachers; and carried out systematically, the principal’s strategy for implementing academic supervision includes: supervising learning tools, supervising using class visit techniques, and observing teacher activities in class, and implementing follow-up on the results of academic supervision in the form of personal and group coaching, Implications of academic supervision school principals, namely: (a) Increasing the ability of teachers in compiling learning tools (b) Increasing the ability of teachers in carrying out the learning process, (c) Increasing the ability of teachers in evaluating student learning outcomes. Academic supervision is one way to increase teacher professionalism in planning, implementing the learning process and evaluating student learning outcomes in order to improve the quality of learning so that both local and national educational goals can be achieved well.